Reading Questions Analysis: English Textbook for SMAN Kota Padang - Elsy Fitri Yana; Yetti Zainil (Universitas Negeri Padang, 2019)
This research was a descriptive research that aimed to analyze the reading comprehension questions in English textbook by using Higher Order Thinking Skill. The data used in this research is reading comprehension questions of English textbook grade X, XI, and XII which is used in SMAN Kota Padang. There are four schools to be inspected and the writer found 10 English textbooks. This study used instrument in the form of indicators from HOTS criteria and Bloom’s Taxonomy Revision criteria. From the result of the reading comprehension question in English textbook by using Higher Order Thinking Skill at SMAN Kota padang, it showed that the reading comprehension questions had used the HOTS criteria. As a result of the analysis in reading comprehension questions, 425 questions (23,09%) Higher Order Thinking Skill questions were found in the reading comprehension questions in 10 English textbooks. The result of this research also found that mostly-used HOTS criteria in the reading comprehension questions is evaluating category.